If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6+5x=-6
We move all terms to the left:
6+5x-(-6)=0
We add all the numbers together, and all the variables
5x+12=0
We move all terms containing x to the left, all other terms to the right
5x=-12
x=-12/5
x=-2+2/5
| 12=3/4y-1 | | 12=4y-1/3 | | 12=4y-5/6 | | 16-2t=t-9+4t | | 8r-15=10r+3 | | 8/2x+1=3 | | 4.5=0.5nn=n= | | 5/6=5x-4/2 | | 57.25=41.3+0.5p | | 5(x-6)=4(x+2) | | 3/4=4y-5/6 | | y-3/8=1/2 | | 10(x-2)=-20x | | 121=11m | | X+2/6=x-3 | | (5x+1)+(4x+17)+90=180 | | 4x-30+3x+10=180 | | (4x-9)+(6x+2)+x=180 | | -5/8(x+3)=10 | | 11x+5=6x+90 | | -4x+6=3x-29 | | 11+18=12x-11x | | 7+d/5=25 | | 6(p+3)=24 | | 10m-2/5=-23 | | -24=4(z+7) | | 0=70-4.9t^2 | | -4×+2y=-16 | | 7x*8x=(5x+3)*(10x-2) | | 5x+3x-60+5x+x=360 | | 3/b+1=5 | | 3x-4x-x=18-6 |